Anticipandose al cambio: guia para el uso de escenarios como instrumento para el manejo forestal adaptable - Wollenberg, Eva Karoline; Edmunds, D.; Buck, L. (Center for International Forestry Research, 2002)
Scenario methods can be used to anticipate the future and expand the creativity of people thinking about complex forest management situations. This manual describes the use of scenarios with multiple stakeholders, with examples drawn from community-based forest management. Four classes of scenario methods are described: visions, projections, pathways and alternative scenarios. Examples of rapid participatory techniques relevant to scenario methods are also summarized. It is hoped that these methods will be useful for bringing together different groups of people concerned about forest management to exchange views, expand the realm of decision possibilities and reach more innovative solutions.